AN ANALYSIS OF LEARNERS’ SOLUTION STRATEGIES IN THE CONTEXT OF MODELLING TASKS - Reit, Xenia-Rosemarie; Schäfer, Marc (Journal on Mathematics Education, 2020)
It remains a challenge for teachers to integrate modeling tasks in everyday mathematics classes. Many studies have been conducted that show the difficulties faced by teachers.  One of the challenging aspects in this regard is that of assessment. In the present study, a connection between structures of learners’ solution strategies and cognitive considerations is established to develop a practice-oriented instrument to determine and assess the complexity of solution strategies of modeling tasks. In this paper, the selected learners’ strategies’ structure was analyzed in-depth to identify the underlying cognitive structure. The results show that thought operations carried out in parallel complicated a solution strategy.  However, the results also support a purely sequential thought operation approach without weighting parallel thought operations, which corresponds to an intuitive assessment procedure by mathematics teachers. As assessment is a great challenge for many teachers in the context of modeling tasks, this study provides a promising frame of reference for further research in this important domain of assessment and modeling.